Proposition of a marketing plan to export portuguese still wines to France - Jullien, Robin Nathan (2015)
The purpose of this thesis is to design a marketing plan to promote Portuguese qualitative still wines in France. Portugal is an old and traditional winemaker. The country has started a vast plan of restructuration of its vineyards and wine production toward quality over the last decades. Portuguese wines do have nowadays very interesting price/quality ratios and are grabbing more and more medals at international wine competitions. In the meanwhile, the French consumption of wine is shifting from traditional and local-oriented habits to a more opened and diversified consumption. Despite the success of many foreign wine regions in France, and the strong links existing between France and Portugal, the Portuguese still wines still have not succeeded to reach the French market. The purpose of this thesis is to outline the strengths and the advantages of the Portuguese wine production according to the characteristics of the French wine market, in order to design a marketing plan to promote qualitative still Portuguese wines to the French customers.